2017
DOI: 10.1007/s00125-017-4258-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of rapid progressors to type 1 diabetes among children with HLA-conferred disease susceptibility

Abstract: Aims/hypothesis In this study, we aimed to characterise rapid progressors to type 1 diabetes among children recruited from the general population, on the basis of HLA-conferred disease susceptibility. Methods We monitored 7410 HLA-predisposed children participating in the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) study for the development of beta cell autoimmunity and type 1 diabetes from birth over a median follow-up time of 16.2 years (range 0.9-21.1 years). Islet cell antibodies (ICA) and aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 34 publications
2
34
2
1
Order By: Relevance
“…20 The Finnish Type 1 Diabetes Prediction and Prevention study showed no sex differences in the development of any single or multiple autoantibodies 21 or in the disease progression after seroconversion. 22 In contrast, female sex was reported to be a clear risk factor for progression from multiple autoantibodies to T1D in the Environmental Determinants of Diabetes in the Young study. 23 Overall, there is limited information on potential sex differences in the autoantibody profile at the presentation of T1D.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…20 The Finnish Type 1 Diabetes Prediction and Prevention study showed no sex differences in the development of any single or multiple autoantibodies 21 or in the disease progression after seroconversion. 22 In contrast, female sex was reported to be a clear risk factor for progression from multiple autoantibodies to T1D in the Environmental Determinants of Diabetes in the Young study. 23 Overall, there is limited information on potential sex differences in the autoantibody profile at the presentation of T1D.…”
Section: Introductionmentioning
confidence: 93%
“…In the prospective BABYDIAB study recruiting infants with at least 1 family member affected by T1D, the cumulative incidence of autoantibodies was similar in both sexes but the peak incidence was observed earlier in boys than in girls . The Finnish Type 1 Diabetes Prediction and Prevention study showed no sex differences in the development of any single or multiple autoantibodies or in the disease progression after seroconversion . In contrast, female sex was reported to be a clear risk factor for progression from multiple autoantibodies to T1D in the Environmental Determinants of Diabetes in the Young study .…”
Section: Introductionmentioning
confidence: 96%
“…In addition, class I HLA genes have been associated with T1D. Young age, autoantibody profiles, and higher prevalence of non‐HLA FUT2 (fucosyltransferase 2) SNPs with predisposing HLA‐risk genes may characterize rapid disease progression in children . Aberrant T‐cell profiles are also linked to T1D.…”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…Faster rates of progression are observed with 3 or 4 versus 2 islet autoantibodies [25,70,71] . The presence of antibodies to IA-2 and ZnT8 as well as higher titers of antibody to Insulin and IA-2 are associated with a faster rate of progression [10,70,[72][73][74] . Islet autoantibody seroconversion at a young age is associated with a faster rate of progression [25] , and disease progression is also accelerated in children at stage 1 T1D with an increased BMI [75] and markedly accelerated in Hispanic children younger than 12 years of age who are overweight or obese [76] .…”
Section: Progression From Stage 1 T1dmentioning
confidence: 99%
“…In contrast to genetics, environmental etiologies have not been validated and thus do not currently contribute to subject stratification in T1D prevention trials. However, some examples of gene-environment interactions include the interactions of the microbiome with the Fut-2 nonsecretor gene polymorphism, which increases risk of T1D and is associated with faster progression of presymptomatic T1D [10][11][12] , and interactions of picornaviruses, which include enteroviruses, with polymorphisms of the innate immunity viral RNA receptor gene region IFIH1(MDA-5) [13,14] .…”
Section: Introductionmentioning
confidence: 99%